З історії Головного військово-історичного музею-архіву при Ґенеральному штабі Української Народної Республіки - Машталір, В. (Український історичний журнал, 2019)
Розглядається діяльність Головного військово-історичного музею-архіву при
Ґенеральному штабі УНР під час його розташування в польському місті Тарнові, де на той час перебував уряд УНР в екзилі. Висвітлено передумови створення, функціонування, здобутки та долю установи. Проаналізовано зусилля
її керівника М.Обідного з реалізації його основних ідей щодо поліпшення музейної роботи, а також встановлення контактів з українськими еміґраційними осередками в Польщі та поза її межами – у Румунії, Болгарії, Туреччині,
Італії, Швеції. Сконцентровано увагу на організаційному аспекті збирання, упорядкування, реєстрації та збереження наказів, щоденників бойових подій, листування й інших військових документів історичного характеру, а також
усіх матеріалів періоду національної революції, зокрема відозв, оголошень, газет і журналів, присвячених українській проблематиці. The article is devoted to the analysis of the activity of the Main Military-Historical
Museum-Archive at the General Staff of the UPR. The article outlines the
preconditions for the creation, functioning, achievements and fate of the mentioned
museum-archive. The work of director M.Obidnyi is analyzed concerning the
implementation of his main ideas on improving the museum work of the Ukrainian
military-historical institution. The activity of M.Obidnyi on establishing contacts
with Ukrainian emigration centers in Poland and beyond in Romania, Bulgaria,
Turkey, Italy and Sweden. The article attempted to focus on the organizational aspect
of collecting, organizing, registering and preserving orders, diaries of combat events,
correspondence and other military documents of a historical nature, as well as all
materials of the Age of the Liberation Movements of 1917–1921, including appeals,
advertisements, newspapers and magazines, devoted to Ukrainian problems. The
activity of the archive museum during its location was studied in the Polish city
of Tarnów, where at that time the UPR Government was in the exile. The facts
of the commitment of the leadership of the Military Ministry of the UPR to the
replenishment of the funds of the Main Military Historical Museum-Archive under
the General Staff of the UPR and the issuance of circulars and orders regarding the
collection and preservation of historical documents on the military path of the UPR
Army are highlighted. The author paid attention to the insufficient funding of the
institution and the efforts of the Polish authorities to transfer the museum-archive to
the camp of interned Ukrainian soldiers and the constant threat of the cessation of
the museum-archive activity. The fact that the institution was transferred from the
Military Ministry to the Ministry of National Education of the UPR was analyzed.
It was found that the decision in general had a negative effect on the further activity
of the museum-archive, since it was subordinated to one of the least financially
secured ministries of the UPR. The above-mentioned led to the fact that in 1923,
M.Obidnyi acted with the initiative of transporting assemblies from Poland to Praha.
The initiative was not supported by the leadership of the UPR. In spite of this, in September 1923 he removed some of the materials from Tarnów to Praha, where they were the basis of the collection of the newly created Ukrainian National Museum-Archive.